The Enteric Nervous System and Its Emerging Role as a Therapeutic Target - Mark A. Fleming; Lubaina Ehsan; Sean R. Moore; Daniel E. Levin (Gastroenterology Research and Practice)
The gastrointestinal (GI) tract is innervated by the enteric nervous system (ENS), an extensive neuronal network that traverses along its walls. Due to local reflex circuits, the ENS is capable of functioning with and without input from the central nervous system. The functions of the ENS range from the propulsion of food to nutrient handling, blood flow regulation, and immunological defense. Records of it first being studied emerged in the early 19th century when the submucosal and myenteric plexuses were discovered. This was followed by extensive research and further delineation of its development, anatomy, and function during the next two centuries. The morbidity and mortality associated with the underdevelopment, infection, or inflammation of the ENS highlight its importance and the need for us to completely understand its normal function. This review will provide a general overview of the ENS to date and connect specific GI diseases including short bowel syndrome with neuronal pathophysiology and current therapies. Exciting opportunities in which the ENS could be used as a therapeutic target for common GI diseases will also be highlighted, as the further unlocking of such mechanisms could open the door to more therapy-related advances and ultimately change our treatment approach.